How to select, collect, interpret, organize, and write your term paper. - Sanderlin, David (Woodbury, N.Y., 1975)
Summarized below are seven steps in the preparation of an historical research paper.: identify history, select a subject and collect information, interpret and organize your information,write your paper, reflect upon the present.
Keywords: Lịch sử,History; Nghiên cứu,Research